1994
DOI: 10.1080/00039896.1994.9937470
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution and Daily Mortality in Residential Areas of Beijing, China

Abstract: The relationship between air pollution and daily mortality in 1989 was examined in two residential areas in Beijing, China. Very high concentrations of sulfur dioxide (SO2) (mean = 102 micrograms/m3, maximum = 630 micrograms/m3) and total suspended particulates (TSPs) (mean = 375 micrograms/m3, maximum = 1,003 micrograms/m3) were observed in these areas. Daily counts of deaths were regressed, using Poisson regression on the logarithm of (SO2) and/or TSPs controlling for effects of temperature, humidity, and da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
98
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(107 citation statements)
references
References 13 publications
8
98
0
1
Order By: Relevance
“…The mortality risk was estimated to increase by 11% with each doubling in SO 2 concentrations (averages were 120 and 67 g/m 3 in 1998 and 2002, respectively). A significant association was also found between TSP and mortality by Xu et al 53 Dong et al 55 found a statistically significant association between air pollution levels and daily mortality during 1990 and 1991. The influence of TSP on patients with cardiovascular disease and of SO 2 on patients with respiratory disease was greater than that on other patients.…”
Section: Adverse Health Impactsmentioning
confidence: 72%
See 1 more Smart Citation
“…The mortality risk was estimated to increase by 11% with each doubling in SO 2 concentrations (averages were 120 and 67 g/m 3 in 1998 and 2002, respectively). A significant association was also found between TSP and mortality by Xu et al 53 Dong et al 55 found a statistically significant association between air pollution levels and daily mortality during 1990 and 1991. The influence of TSP on patients with cardiovascular disease and of SO 2 on patients with respiratory disease was greater than that on other patients.…”
Section: Adverse Health Impactsmentioning
confidence: 72%
“…In Beijing, China, Xu et al 53 found a significant association between SO 2 levels and daily mortality throughout the year. The mortality risk was estimated to increase by 11% with each doubling in SO 2 concentrations (averages were 120 and 67 g/m 3 in 1998 and 2002, respectively).…”
Section: Adverse Health Impactsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Studies of daily mortality in relation to temperature show less consistent results, probably reflecting physiological and social adaptation to local conditions. The dose-response relationship between temperature and mortality is generally 'U-shaped', with increases in mortality at low and high extremes of temperatures.…”
mentioning
confidence: 99%
“…There has been little integrated assessment about the external costs of road transportation for society, despite a number of studies on vehicle pollution and related health problems (Xu, 1994;Xu, et al 1995, pp.286-89;James and Polenske, 1998). These external costs include the 14 Eighteen cities and provinces, such as Beijing, Shanghai and Guangzhuo, imposed local laws to ban the use of leaded gasoline in 1998.…”
Section: Costs Of Externalitiesmentioning
confidence: 99%